Montessori Method in Academic Flow Development - Nabila Qurrotu Aini; Rahma Sakina (Research Collaboration Community (RCC), 2020)
This research aimed to describe the implementation of the Montessori Method in academic flow development for students. A Qualitative approach and intrinsic case study design were used in this research. The participants of this research were five students of the Arabic Language Study Program in one of university in Bandung, West Java. The participants were selected using purposive sampling technique. The findings revealed that students were able to achieve academic flow, which was marked by the achievement of all indicators in the aspect of absorption by activity. However, the indicator of thinking included in the aspect of fluency by performance was difficult to be achieved by the students. The results of this research are expected to be utilized by those who play a role in developing students' potential, which was guidance and counseling service units based in universities and academic supervisors.